Service quality and students’ satisfaction with the professional teacher development programmes by distance mode in a South African university - Oduaran, AB (South African Journal of Higher Education, 2011)
This article reports on the relationship between seven factors that described dimensions of education service quality and overall service quality on one hand, and students’ satisfaction with the professional teacher development programmes by distance mode in a South African University on the other. We sought to find out whether students enrolled in the Advanced Certificate in Education and National Professional Diploma in Education academic programmes offered by distance mode by the School of Continuing Education were satisfied with the quality of service delivery. We were also interested in finding out the factors that contributed most to students’ satisfaction with academic programme delivery. The dependent variable in this study was held to be the overall student satisfaction and the independent variable was the education service quality that measured the level of students’ satisfaction or dissatisfaction with the service performance. The sample consisted of 313 respondents randomly selected from a population of 916 students enrolled in the School. Data were collected by means of a questionnaire that was tested for validity and reliability. The major finding was that the correlation coefficients of all the clustered quality dimensions and student satisfaction were significantly correlated at 95 per cent confidence level (i.e. P = .05, meaning that the students were largely satisfied). The implication of this correlation is that all service quality dimensions were significantly correlated with student satisfaction as well as significantly correlated with themselves, and this was deemed as good enough for an academic programme that is delivered by distance mode.